PERAN FINANCIAL TECHNOLOGY DALAM MENGHIMPUN DANA ZAKAT, INFAQ DAN SEDEKAH SERTA KONTRIBUSINYA DALAM MENANGGULANGI KEMISKINAN DI INDONESIA - Jamal, Mulyono; Putri, Nurmalasari Mulia; Zahro’, Khurun’in (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2024)
Financial technology (Fintech) is present as a solution in distributing zakat funds, which is predicted to reduce poverty levels. However, so far it is still not optimal. This causes a reduction in public knowledge and awareness of fintech. This research aims to analyze the role of financial technology in collecting ZIS funds and its contribution to overcoming poverty in Indonesia. This type of research is descriptive qualitative with a literature study approach. The results of this research show that financial technology can maximize ZIS fund collection. This is proven by the increasing number of muzakki and infaq and alms donors so that they can be distributed to those in need.